2014
DOI: 10.1007/s10354-014-0265-1
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic pain

Abstract: Pain is a common symptom of many diseases. Recently, the pain has been classified and analyzed exactly. Its particular components/types are described to the maximum of their depths and details. That is why each particular pain present in a specific disease (pancreatopathies included) has to be treated according to the presence of the specific type of pain. In diseases of pancreas, there are nociceptive, neuropathic, and inflammatory components of pain participating, frequently. Especially long-lasting, not wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Pancreatic sensory innervation is mostly sympathetic; cell bodies of pancreatic afferent nerves are located in the dorsal root ganglion (DRG) at T5-L2 and are activated in AP [60]. When mechanical or chemical stimuli destroy acinar cells, digestive enzymes and increased inflammatory mediators are released in the vicinity [61]. These mediators include K+, H+, ATP, histamine, substance P (SP), bradykinin, prostaglandins, and norepinephrine, all of which further amplify the inflammatory response [61,62].…”
Section: Inflammatory Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic sensory innervation is mostly sympathetic; cell bodies of pancreatic afferent nerves are located in the dorsal root ganglion (DRG) at T5-L2 and are activated in AP [60]. When mechanical or chemical stimuli destroy acinar cells, digestive enzymes and increased inflammatory mediators are released in the vicinity [61]. These mediators include K+, H+, ATP, histamine, substance P (SP), bradykinin, prostaglandins, and norepinephrine, all of which further amplify the inflammatory response [61,62].…”
Section: Inflammatory Painmentioning
confidence: 99%
“…When mechanical or chemical stimuli destroy acinar cells, digestive enzymes and increased inflammatory mediators are released in the vicinity [61]. These mediators include K+, H+, ATP, histamine, substance P (SP), bradykinin, prostaglandins, and norepinephrine, all of which further amplify the inflammatory response [61,62].…”
Section: Inflammatory Painmentioning
confidence: 99%
“…It has been reported that HMGB1 is involved in the development of visceral pain associated with pancreatitis and cystitis (Table 2). Patients with pancreatitis or pancreatic cancer frequently experience severe pancreatic pain that has nociceptive, inflammatory and neuropathic components of pain (Nechutova et al, 2014). Clinical reports have shown that serum HMGB1 levels increase in patients with severe acute pancreatitis and are correlated with severity or poor prognosis of pancreatitis (Arriaga‐Pizano et al, 2018; Yasuda et al, 2006).…”
Section: A Role Of Hmgb1 In Pain Processingmentioning
confidence: 99%
“…Studies employing a rat model of neuropathic pain induced by tibial nerve injury (TNI) indicate that glycyrrhizin, a possible direct HMGB1 inhibitor, and an anti-RAGE-neutralizing antibody reduce the TNI-induced mechanical hyperalgesia in the rat hindpaw and that TNI increases cytoplasmic HMGB1 levels in DRG neurons and expression of RAGE in the DRG tissue (Allette et al, 2014;Feldman et al, 2012). Studies employing a mouse model of neuropathic pain induced by partial sciatic nerve ligation (PSNL) show that single systemic administration or perineural injection of an anti-HMGB1-neutralizing antibody reverses the continuing allodynia in the delayed phase of PSNL-induced neuropathic pain in mice and that PSNL increases expression of HMGB1 in the DRG neurons and in macrophages and Schwann cells adjacent to neuronal fibres in the sciatic nerve (Nakamura et al, 2013;F. F. Zhang et al, 2016).…”
Section: Neuropathic Pain Caused By Surgical Nerve Injurymentioning
confidence: 99%
“…DRGs are responsible for receiving all the nerve impulses from the body receptors and transmitting them to the spinal cord. In the diseases of the pancreas, there are nociceptive, neuropathic, and inflammatory components of pain; among them, neuropathic pain is caused by damage to nerve endings within the pancreas and by changes in the neural plasticity of the peripheral nervous system and the central nervous system [24]. Our work builds on these studies, and for the first time, we focused on the nerves that innervate the pancreas.…”
mentioning
confidence: 99%